A Gamification-Based Approach to Enhance Student Engagement and Attendance in High School Education - Martin Junior, Lucas Gonzalez; Souza, Francisco Carlos M.; Souza, Alinne C. Correa (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2025)
This study explores the design of Class Cup, a gamification approach to enhance student attendance, engagement, and participation that was implemented in a non-profit institution located in southeastern Brazil. The initiative confronts a critical educational challenge: low student engagement and elevated dropout rates. Class Cup aims to reframe school participation as a collective and competitive experience by utilizing team-based point systems, dynamic leaderboards, and tangible rewards. We conducted an exploratory case study to evaluate the Class Cup approach through the perceptions of 159 high school students and six teachers across five classes. After a semester of implementation, 80% of the classes showed improved attendance, resulting in an average increase of 6.22%. The results underscore the potential of a gamified approach to drive measurable behavioral change in educational settings.